IMPLEMENTASI PLTS PADA SISTEM OTOMATIS PEMBERIAN NUTRISI TANAMAN SAYUR BERBASIS LoRa - Arifin, Muhamad Arifin Prastyono; Priyandoko , Gigih; Effendy, Dedi Usman (Program Studi Teknik Elektro - Fakultas Teknik - Universitas Widyagama Malang, 2024)
The agricultural sector deals with most of human food needs; people are starting to think about making new agricultural innovations. Precision Agriculture (PF) is an agricultural land management system that uses technology to make the best decisions for a specific goal and know what is needed for crop growth. This study utilizes LoRa technology as a data transmission medium, enabling users to remotely observe farming conditions and address issues related to crop irrigation. With this technology, the process of plant watering and nutrition delivery will be carried out automatically using predefined time parameters. The results of this study, routine and scheduled nutrition spraying according to the needs of plants done twice a day, is expected to help harvest with optimal yields as well as make it easier for farmers to perform digital care even if farmers are very far away from the garden.